Penggunaan Akronim di Media Sosial - Riri Amanda Fitriana; Fitri Yulinda; Yana Febriani (Lembaga Pengembangan Kinerja Dosen, 2024)
Language allows us to communicate, teach, learn, and maintain culture. Each language has specific grammatical rules and vocabulary, which reflect the values, norms and beliefs of the society that uses it. A dynamic language does not rule out the possibility that more and more users will become creative. However, it is important to remember that changes that are too rapid will have an impact on the continuity of the language itself. This research aims to identify the use of acronyms in prokem language or slang. The research results show that acronyms are increasingly commonly used in everyday life. Acronyms are used to save time and space, and to simplify messages. However, excessive or unclear use of acronyms can confuse readers and hinder understanding of the message. For this reason, there is a need for guidance regarding this acronym.